(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This study aims to explore the contributions of pragmatics to the development of discourse-analysis mechanisms by examining the interaction between linguistic structure and pragmatic context in the production of meaning. The research is based on the assumption that discourse comprehension cannot be achieved solely through linguistic elements; rather, it requires consideration of the communicative circumstances and contextual factors related to both the speaker and the listener. The analytical method was employed to examine a set of discourses, with a focus on key pragmatic concepts such as intentionality, implicature, and presupposition. The findings reveal that pragmatics provides precise tools for discourse analysis and for understanding its communicative and persuasive dimensions, making it one of the fundamental approaches in contemporary linguistic studies.